The Impact of Islamic Education on Social Media on the Beliefs of the Muslim Community - Najamuddin, Andi (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Social media serves as an alternative medium for disseminating da'wah messages, prompting many da'wah practitioners to utilize it as a platform. The complexity of media requires da'i to engage with it, particularly social media, which serves as an efficient medium for da'wah communication in contemporary society. This literature review seeks to assess the efficacy of da'wah messages disseminated through social media based on the beliefs of the Muslim population. A broad examination of the efficacy of da'wah media is necessary due to the rapid evolution and utilization of media. This study uses a literature review methodology, collecting various sources from journals, articles, and books related to the research variables. The literature review is analyzed based on the specifications of the last 10 years, between 2015 and 2025. The findings of this literature review indicate that the efficacy of social media da'wah depends on the frequency and intensity of one's engagement with the media, after which the message conveyed is relevant to the da'wah discourse.